Assessing Chemistry Teachers’ Knowledge of Atmospheric Chemistry Associated with Environmental Chemical Literacy - Erfan Priyambodo (Indonesian Journal of Chemistry and Environment, 2023)
Environmental chemical literacy (ECL) is part of environmental literacy which is one of the most abilities of a citizen for sustainable development. The data for this study were collected using a cross-sectional survey technique for high school chemistry teachers. The data was obtained through online test in atmospheric chemistry, which is consists of 4 topic, i.e. particulate matter (PM) 2.5, green house gasses correlated to global warming, ozone depletion and acid decomposition. Based on the study, it showed that two thirds of respondents have moderate ability in atmospheric chemistry associated with ECL.